EVALUATION OF THE TOTAL QUALITY MANAGEMENT OF SOLAR POWER PLANTS AT IBU KOTA NUSANTARA, INDONESIA - Surayya Mappangile, Andi; Zainal, Isradi; Zain, Abdul; Radhiansyah, Radhiansyah (Jurnal GeoEkonomi, 2025)
The construction of a Solar Power Plant or PLTS in the new capital city of Indonesia or IKN Nusantara need quality management to meets expectations of the government, societies and stake holders. In order for achieve this expectation, the quality of the solar power plant must be guaranteed, safe, secure and not damage the environment. The aim of this research is to evaluate the implementation of Quality Management in IKN. The analytical method used in this research is descriptive qualitative. Evaluation is based on the main elements of Quality Management Practices such as obsession with quality, scientific approach, long-term commitment, teamwork, education and training, controlled freedom, unity of purpose, employee involvement and empowerment The result of the research indicates that the construction of Solar Power Plant (PLTS) in the new capital city of Indonesia or IKN Nusantara fulfil the requirements of Quality Management